(untitled) (GEOmedia, 2010)
NSDI 2.0: are we ready? "Powering our National Economy, Renewing our Infrastructure, Protecting our Environment” is the concept behind the design of the american NSDI 2.0: this will lead to the start of a second generation of Spatial Data Infrastructures that will bring economical benefits to all the traditional infrastructures such as distribution, communication, utilities and and energy networks. The article provides an analysis on the italian context as well.